A brand-new catalytic system: a Pd-based catalyst directly attached on the inner walls of the reactor which independently catalyzed the Heck reaction1. Issue 69 (29th July 2015) - Meng, Qingrun; Bai, Jie; Li, Chunping
<x xml:space="preserve">Abstract</x> A Pd-based catalyst directly attached on the inner surface of the reactor as a new catalytic system has been achieved and developed via an electrospinning technique followed by an impregnation–reduction and a simple carbonization process.